Study on the relationship among the urbanization process, ecosystem services and human well-being in an arid region in the context of carbon flow: Taking the Manas river basin as an example. (December 2021) - Liu, Ranran; Dong, Xiaobin; Wang, Xue-chao; Zhang, Peng; Liu, Mengxue; Zhang, Ying
Graphical abstract: The relationship between carbon cycle and urbanization, ecosystem services and human well being. Highlights: Quantified urbanization, ecosystem services and human well-being with carbon as the medium. Analyzed the restrictive effect of urbanization on ecosystem service and the impacts of urbanization and ecosystem services on human well-being. Constructed the urban development benefit index from the perspective of human well-being. Discussed the significance of carbon emission reduction on the high-quality and sustainable development. Abstract: The complex interaction among urban socioeconomic development, ecosystem services and human well-being is related to the level of regional sustainable development, which is an important cross scientific issue in the study of natural ecosystems and the social economy and is also an important subject in the study of the "future Earth". This research quantitatively evaluated the level and the spatial and temporal dynamic characteristics of urbanization, ecosystem services and human well-being in Manas River Basin with carbon elements as the carrier. Then the complex relationships and action mechanisms among the three was revealed by using an approach comprising constraint lines, the urban development benefit index and a correlation analysis. The results showed that urbanization and all its dimensions increased to varying degrees from 2000 to 2015. For the ecosystem services, except for provision services, the other ecosystem services showed a fluctuating downward trend, affected by which human ecological well-being also showed the same trend, while social well-being, economic well-being and total human well-being showed exponential growth. Spatially, in addition to the provision services, the distribution of the other ecosystem services had an obvious spatial differentiation with urbanization. And broadly, the distribution trend showed that the farther away from the city centre an area was, the higher the services level. The constraint line analysis showed that each dimension of urbanization had a significant constraint on the ecosystem services, and the constraint relationship showed the hump type, logarithmic type, and negative line type, which indicated that the potential maximum value of the basin ecosystem services decreased with the improvement of urbanization level. Meanwhile, the extensive urban development made the benefit of urban development of the river basin decline. The correlation analysis showed that human well-being was more affected by urbanization than ecosystem services, especially economic urbanization and land urbanization, which remarkably improved human well-being. However, in the long run, the decline of ecological well-being caused by urbanization will affect the growth potential of human well-being. This study provides a theoretical support and suggestions for the formulation of urban development strategies and the realization of low-carbon and high-quality development for the basin.